Human Body Donation to Anatomy Laboratory for Educational Purpose: Legal, Ethical and Religious points of view - Shrestha , Sunil; Shrestha , Shamsher; Timsina , Ram Prasad; Amgain , Kapil (Europasian Journal of Medical Sciences, 2021)
Body donation refers to whole body donation for teaching and learning processes considered a noble act. In most religions, body donation law, organ transplantation act, tissue act permits body donation for medical and research purposes. In the current article, we have discussed mainly body donation laws of different countries along with necessary criteria that should be fulfilled by body donors along with the law that is necessary to claim the unclaimed bodies and give consent for the body donation. The article also includes a brief view regarding the religious perspective of major religions about human body donation. DOI: https://doi.org/10.46405/ejms.v3i2.363